Terahertz quantum cascade laser array with spatially-separated beams. (November 2021) - Li, Yuan-Yuan; Zhao, Fang-Yuan; Ma, Yu; Li, Wei-Jiang; Liu, Jun-Qi; Liu, Feng-Qi; Luo, Jun-Wei; Zhang, Jin-Chuan; Zhai, Shen-Qiang; Zhuo, Ning; Wang, Li-Jun; Liu, Shu-Man
Highlights: A compact lens-coupled THz QCL array with multiple spatially-separated beams has been realized. Excellent emission characteristics of low divergence angles from 4.1°×3.5° to 7.2°×5.8° and multi-wavelength spectra are obtained. The angular deviation of 10° between adjacent laser guarantees the spatial separation of beams without overlap. The output intensity after lens improves dramatically for lasers at different positions with a high focusing efficiency. Abstract: A lens-coupled terahertz (THz) quantum cascade laser (QCL) array with multiple spatially-separated beams is presented. The beam divergence and focusing efficiency after lens are both investigated by simulations and experiments. By integrating an appropriate hyper-hemispherical silicon lens with a well-designed six-element distributed feedback (DFB) QCL array inside the cryostat window, excellent emission characteristics of small divergence angles from 4.1°×3.5° to 7.2°×5.8° and multi-wavelength spectra are realized at 77 K. The deflection angle between adjacent beams is 10°. The output intensity after lens is 113 to 25 times that of original beams with a focusing efficiency ranging from 58% to 37% for lasers at different positions. This method provides a simple solution to form a multi-beam THz source with high intensity and low far-field divergence.